Temporal Profile of Cerebrovascular Reactivity Impairment, Gray Matter Volumes, and Persistent Symptoms after Mild Traumatic Head Injury - da Costa, Leodante; van Niftrik, Christiaan Bas; Crane, David; Fierstra, Jorn; Bethune, Allison (Frontiers in Neurology, 2016)
Objective: There has been increased awareness to neurocognitive issues after mild traumatic brain injury (mTBI), and despite ongoing progress, established imaging markers for mTBI are so far not available. It has been suggested that mTBI impairs cerebrovascular reactivity to CO2 (CVR), which could be related to post-concussion symptoms (PCS). We investigate the evolution of CVR after mTBI using blood-level oxygen dependent magnetic resonance imaging (BOLD MRI) and its possible correlation with PCS. Methods: A prospective cohort (25 mTBI and 18 matched controls) was submitted to blood-oxygen level dependent (BOLD) magnetic resonance imaging (MRI) CVR measurements at 2 time points (average 60 and 180 days) after injury. Symptoms were assessed with the Symptom Severity Score (SSS) and Sports Concussion Assessment Tool 2 (SCAT-2). SSS and SCAT2, CVR and brain volume - grey and white matter, whole brain (GM, WM and WB), age and sex where examined and compared between groups and time points. Results: Age and sex distribution was similar. SSS and SCAT2 scores were significantly different (p=0.0001) between groups. SCAT2 scores tended to improve in mTBI patients (p=0.07), although follow-up scores were still lower than controls (p=0.0007). Brain volumes were similar at first visit (white matter p=0.71; grey matter p=0.36). In mTBI there was a reduction in grey matter volume between visits 1 and 2 (p=0.0046). Although mean CVR indexes were similar (WM p=0.27; GM p=0.36; WB p=0.35), the correlation between SCAT2 and CVR was negative in controls (WM-r=-0.59; p=0.010; GM-r=-0.56; p=0.016; brain-r=-0.58; p=0.012) and weaker and positive in mTBI (brain-r=0.4; p=0.046; GM-r=0.4; p=0.048). SCAT2 correlated with GM volume (r=0.5215, p=0.0075) in mTBI but not in controls (r=0.29, p=0.23). Conclusion: There is a correlation between lower GM CVR indexes and lower performance on SCAT-2 in patients with mild traumatic brain injury, which seems to be associated with more symptoms. This correlation seems to persist well beyond 120 days. Mild traumatic brain injury may lead to a decrease in GM volume.